A opereta A Princesa do Catete, de Euclides Fonseca (1854-1929): estudo cênico-musical e edição - Melina de Lima Peixoto (2023)
This dissertation is about the chamber operetta A Princesa do Catete by Euclides Fonseca (1854-1929), composed based on the libretto created by Carneiro Vilela (1846-1913). Data about the genesis of this work, followed by biographical information about the creator of its music and the author of its libretto, and a scenic organization proposed by this author are the main questions that structure this research. In addition to the organization into three chapters dedicated to the understanding of A Princesa do Catete as a product of the Brazilian Belle Époque, this thesis is completed by the presentation of a Performance Edition of its score, followed by a critical apparatus that points out questions and solutions arising from the observation of the score, autograph manuscript, belonging to the Instituto Ricardo Brennand 3 IRB, located in Recife, PE. As a methodological process, this author used the works designed by Borém (2019), author of the Edip tool, and also by Figueiredo (2017), whose definition of editing types greatly contributed to the final format of the score for A Princesa do Catete, presented as an Annex to this work.